Faktor Determinan Kurangnya Pencapaian Target Imunisasi Dasar Lengkap di Puskesmas Kurulu Distrik Kurulu, Kab. Jayawijaya Papua - Susianike Oktaviani Maega; Maryati Sutarno (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Complete basic immunization coverage in Papua is still far from the national target of 90%, with only 70% in Papua, 75% in West Papua, and around 10% in Papua Mountains. This reflects the gap in access and implementation of immunization. In Papua Mountains, health cadres have a vital role due to limited medical personnel and health facilities. They are the main link between the community and immunization services, ensuring that children in remote areas continue to receive the immunizations needed to prevent disease. To determine the influence of the role of cadres and the number of children on the achievement of complete basic immunization targets at the Kurulu Health Center, Kurulu District, Jayawijaya Regency, Papua. Using an analytical approach with a cross-sectional method. The number of samples is 133 using the Slovin formula. The data analysis technique uses the Chi-Square test. The results of the Chi-Square statistical test in the cadre role category obtained a p-Value of 0.000 (0.05), while in the number of children category obtained a p-Value of 0.031 (0.05), which indicates that there is a significant influence between the role of cadres and the number of children on the achievement of complete basic immunization targets. There is an influence of the role of cadres and the number of children on the achievement of complete basic immunization targets at the Kurulu Health Center, Kurulu District, Jayawijaya Regency, Papua. For the coordinators of the Health Center and cadres, it is expected to improve coordination and monitoring, as well as provide more intensive education to families, especially those with many children, in order to achieve better immunization targets. Keywords: Achievement of Complete Basic Immunization Targets, Number of Children, Role of Cadres.  ABSTRAK Cakupan imunisasi dasar lengkap di Papua masih jauh dari target nasional 90%, dengan hanya 70% di Papua, 75% di Papua Barat, dan sekitar 10% di Papua Pegunungan. Hal ini mencerminkan kesenjangan akses dan pelaksanaan imunisasi. Di Papua Pegunungan, kader kesehatan memiliki peran vital karena keterbatasan tenaga medis dan fasilitas kesehatan. Mereka menjadi penghubung utama antara masyarakat dan layanan imunisasi, memastikan anak-anak di daerah terpencil tetap mendapatkan imunisasi yang diperlukan untuk mencegah penyakit. Mengetahui pengaruh peran kader dan jumlah anak terhadap capaian target imunisasi dasar lengkap di Puskesmas Kurulu distrik Kurulu, Kab. Jayawijaya Papua. Menggunakan pendekatan analitik dengan metode cross sectional. Jumlah sampel yaitu sebanyak 133 dengan menggunakan rumus Slovin. Tehnik analisis data menggunakan uji Chi-Square. Hasil Uji statistik Chi-Square  pada kategori peran kader diperoleh nilai p-Value 0.000 ( 0.05), sementara itu pada kategori jumlah anak diperoleh nilai p-Value sebesar 0,031 (0,05), yang mengindikasikan bahwa adanya pengaruh yang signifikan antara peran kader dan jumlah anak terhadap pencapaian target imunisasi dasar lengkap. Terdapat pengaruh peran kader dan jumlah anak terhadap capaian target imunisasi dasar lengkap di Puskesmas Kurulu distrik Kurulu, Kab. Jayawijaya Papua. Untuk koordinator Puskesmas dan kader, diharapkan dapat meningkatkan koordinasi dan pemantauan, serta memberikan edukasi yang lebih intensif kepada keluarga, khususnya yang memiliki banyak anak, agar dapat mencapai target imunisasi yang lebih baik. Kata Kunci: Capaian Target Imunisasi Dasar Lengkap, Jumlah Anak, Peran Kader.